Impact of geopolymer aggregate on the mechanical properties and durability characteristics of concrete - Udhaya Kumar, T.; Vinod Kumar, M.; Salunkhe, Sachin; Cep, Robert; Abouel Nasr, Emad (Frontiers in Built Environment, 2024)
This study examined the use of geopolymer aggregate (GPA), produced from slag and an alkaline solution, as a substitute for coarse aggregate in conventional concrete. The research aimed to evaluate how different proportions of GPA (25%, 50%, 75%, and 100% replacement) affect the durability and mechanical properties of concrete. A series of tests were conducted, including slump, compressive strength, flexural strength, chloride resistance, sulfate resistance, sorptivity, and water absorption. The results demonstrated significant improvements in concrete properties with the inclusion of GPA. The compressive strength of GPA concrete ranged from 31 to 38 MPa, showing a 10%–15% increase over that of standard concrete. Flexural strength improved by 6% at 7 days and 7.5% at 28 days compared to control mixes. Water absorption was reduced by 42.58%, and sorptivity decreased by 47.9% compared to ordinary aggregate concrete. GPA concrete also excelled in acid resistance, with a weight loss of 28.6% and a lower reduction in strength compared to traditional acidic aggregates. In sulfate resistance tests, GPA concrete showed a 31% reduction in both weight and strength loss. These results highlight the advantages of using GPA as an alternative to conventional coarse aggregates. GPA not only enhances the mechanical and durability properties of concrete but also presents a more sustainable option, contributing to reduced environmental impacts associated with traditional aggregate materials.